2022
DOI: 10.31083/j.fbl2702062
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Low-Level Er: YAG (2940 nm) laser irradiation on the photobiomodulation of mitogen-activated protein kinase cellular signaling pathway of rodent cementoblasts

Abstract: Backgrounds: Dental avulsion due to trauma, especially in young patients, is a worldwide problem, requiring tooth replacement. Delayed replantation could cause tooth loss when the cementum is severely damaged. A small number of studies has reported that photobiomodulation (PBM) therapy using Er: YAG laser irradiation activates cellular signaling responses in different cell types, resulting in a variety of favorable biological effects. The aim of this in vitro study was to evaluate the potential biostimulatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…The possible effect that exogenous CNTF may exert on the cell viability of OCCM-30 cells was examined calorimetrically using 3-(4,5-dimethylthiazol-2-yl)-5-(3-carboxymethoxyphenyl)-2-(4-sulfophenyl)-2H-tetrazolium (MTS) assay (G3582, Promega, Fernwald, Germany) as previously described [ 33 , 34 ]. Briefly, cells were treated with different concentration of CNTF (0, 50, 100, 200, 400 and 800 ng/mL) in starvation medium over a period of 24 h. IL-6 cytokine served as the positive control.…”
Section: Methodsmentioning
confidence: 99%
“…The possible effect that exogenous CNTF may exert on the cell viability of OCCM-30 cells was examined calorimetrically using 3-(4,5-dimethylthiazol-2-yl)-5-(3-carboxymethoxyphenyl)-2-(4-sulfophenyl)-2H-tetrazolium (MTS) assay (G3582, Promega, Fernwald, Germany) as previously described [ 33 , 34 ]. Briefly, cells were treated with different concentration of CNTF (0, 50, 100, 200, 400 and 800 ng/mL) in starvation medium over a period of 24 h. IL-6 cytokine served as the positive control.…”
Section: Methodsmentioning
confidence: 99%
“…The induction of mineralization by means of mineral deposition amount detection was measured using Alizarin Red staining, as previously described [ 31 ]. Briefly, the extracellular matrix was washed with ice-cold 1 × phosphate-buffer saline (PBS), fixed with fixation buffer (BD Cytofix TM , Thermo Fisher Scientific, Leipzig, Germany) and stained with 2% Alizarin Red solution (Sigma) for 5 min.…”
Section: Methodsmentioning
confidence: 99%
“…Gene set enrichment analysis clarified that Er:YAG laser irradiation enriched Notch signaling, which plays a critical role in various cellular functions including the promotion of osteogenic differentiation of osteoblasts in synergy with BMP [53] . Recently, Yong et al [54] reported that low-level Er:YAG laser irradiation at 2.0 J/cm 2 induces mouse cementoblast (OCCM-30) migration, proliferation and differentiation, and activates the MAPK (ERK1/2, P38 and JNK) signaling pathway.…”
Section: Effects Of Lasersmentioning
confidence: 99%